Wet Nursing: A Historical Review and Its Ideal Characteristics - Zilal, Saari; Farahwahida, Mohd Yusof; Arieff Salleh, Rosman; Tamar Jaya, Nizar; Siti Norlina, Muhamad; Shahrel Ahmad, Shuhel Ahmad (Persatuan Saintis Muslim Malaysia, 2016)
Breastfeeding and wet nursing have been synonymous since ancient times. Each civilization has carved out its own history regarding wet nursing. This article overviews the historical aspect on how wet nursing began and survived the times and briefly look at it from the perspective of Judaism, Christianity and Islam. Also included are factors affecting wet nursing services, that is, social class; occupation; maternal debility; family and friendship ties; as well as myths and taboos. The characteristics of an ideal wet nurse are also discussed from the physical aspects; milk; nutrition; emotion; morality and behaviour. The selection of wet nurse in the form of physical, milk and nutrition are easier to identified. At the same time, characteristics of morality and behaviour is more important to ensure that the life of an infant becomes more pleasant. It is generally believed that children inherit physical and mental features from the source of the milk they consume. Thus, parents are advised to be more mindful in selecting a wet nurse.